Investigation on mechanochemical behavior of Al/Mg–B2O3–Nb system reactive mixtures to synthesize niobium diboride. (May 2015) - Jafari, Majid; Tajizadegan, Hamid; Golabgir, Mohammad Hossein; Chami, Akbar; Torabi, Omid
Abstract: Aluminum and magnesium were used in the M–B2 O3 –Nb (M = Al, Mg) system to synthesize niobium diboride (NbB2 ) via a mechanochemical process. The phase transformation and structural evaluation were investigated by means of X-ray diffractometry, scanning electron microscopy (SEM), transmission electron microscopy (TEM) and differential thermal analysis techniques (DTA). Unlike thermodynamic possibility and DTA results, negligible aluminothermic reaction was occurred in the system and AlNb2 intermediate phase was formed during milling. On the other hand, nanostructure NbB2 was mechanosynthesized by the magnesiothermic reduction after 2.4 h of milling and the type of reactions was mechanically induced self-sustaining reaction (MSR). DTA results revealed that Mg3 (BO3 )2 was largely formed during the thermal process, while the quantity of this by-product extremely decreased during the mechanochemical synthesis and completely eliminated after 5 h of milling. Scanning and transmission electron microscopy observations confirmed that the range of particle size was within 100 nm. Highlights: Niobium diboride has been synthesized starting with Mg, B2 O3 and Nb. Magnesiothermic reaction provided enough heat for activating synthesis reaction. Mg3 (BO3 )2 was largely formed during the thermal process. The range of particle size was within 100 nm.